2023
DOI: 10.3389/fimmu.2022.995715
|View full text |Cite
|
Sign up to set email alerts
|

Spatial genomics reveals a high number and specific location of B cells in the pancreatic ductal adenocarcinoma microenvironment of long-term survivors

Abstract: Background and aimOnly 10% of pancreatic ductal adenocarcinoma (PDAC) patients survive longer than five years. Factors underlining long-term survivorship in PDAC are not well understood. Therefore, we aimed to identify the key players in the tumor immune microenvironment (TIME) associated with long-term survivorship in PDAC patients.MethodsThe immune-related gene expression profiles of resected PDAC tumors of patients who survived and remained recurrence-free of disease for ≥36 months (long-term survivors, n=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…However, the immune-incompetent TME is potentially preventing proper anti-tumour immune responses as can be seen with high levels of CXCR4 on the B cell compartment, potentially restricting their access to the tumour core via retention outside. Indeed, higher number and a specific locations of B cells quality in TME, maturity of TLSs, and neoantigen have been shown in PDAC long-term survivors 16 . These data suggest that patients with higher adaptive cell infiltration may benefit most from boosting the immune response against abortive or dysfunctional TLSs, which may potentially be achieved by cancer vaccines 57 , targeting T cell senescence and/or targeting chemokines.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the immune-incompetent TME is potentially preventing proper anti-tumour immune responses as can be seen with high levels of CXCR4 on the B cell compartment, potentially restricting their access to the tumour core via retention outside. Indeed, higher number and a specific locations of B cells quality in TME, maturity of TLSs, and neoantigen have been shown in PDAC long-term survivors 16 . These data suggest that patients with higher adaptive cell infiltration may benefit most from boosting the immune response against abortive or dysfunctional TLSs, which may potentially be achieved by cancer vaccines 57 , targeting T cell senescence and/or targeting chemokines.…”
Section: Discussionmentioning
confidence: 98%
“…PDAC has been traditionally considered to have a low mutation rate, suggesting a low prevalence of antigens to stimulate the immune response. However, seeing the presence of activated and exhausted cells within the TME, and associations between cytotoxic CD8 T cells, B cells and neoantigen quality with patient survival 16,17 suggests the presence of specific stimuli and warrants the investigation of the clonal distribution and evolution of both T and B cells. Multiple previous studies have shown that higher adaptive immune cell infiltration is associated with marginally better survival 8,18 , however, both adaptive and myeloid enriched PDAC patients have dismal prognosis 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the drastic effects of NeoTx on the immune landscape of PDAC, we further explored the differential association of lymphocyte frequencies with OS in NeoTx and PR patients. So far, contradictory results regarding the prognostic value of CD20 + B cells in PDAC have been published, with several studies describing a positive impact on survival ( 20 , 24 , 77 , 78 ), while one report observed a negative association ( 79 ). A meta-analysis integrating multiple studies reported no link between B cell frequencies and survival in PDAC ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Breg - FcRγ + TAMs crosstalk drives a tumor-promoting macrophage phenotype supporting tumor growth ( 100 ). The spatial organization of immune cells within the TME influences survival and response to therapy in several tumor types, including PDAC ( 101 , 102 ). By comparing transcriptional data of PDAC tissue samples from resected long-term and short-term survivors, a higher infiltration of B cells was observed in long-term survivors.…”
Section: Deciphering Time In Pdacmentioning
confidence: 99%
“…By comparing transcriptional data of PDAC tissue samples from resected long-term and short-term survivors, a higher infiltration of B cells was observed in long-term survivors. Spatial data of long-term survivors revealed the proximity of CD20 + B cells and T cells with an activated effector phenotype, highlighting the importance of studying the differences in immune infiltration in a specific location ( 101 ).…”
Section: Deciphering Time In Pdacmentioning
confidence: 99%